2019
DOI: 10.15408/jti.v12i1.10507
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Technology Acceptance Model Pada Aplikasi Platform Perdagangan Elektronik Di Kalangan Mahasiswa

Abstract: Shopee merupakan platform perdagangan elektronik yang didirikan pada tahun 2009 sebagai pasar mobile-sentris sosial yang pertama dimana pengguna aplikasi shopee ini dapat melakukan belanja, menjual, dan menjelajahi kapan saja melalui ponsel pintar dengan aman dan praktis. Aplikasi Shopee dipengaruhi dari beberapa faktor untuk menghasilkan sistem belanja yang sesuai dengan kebutuhan  penggunanya, tidak menutup kemungkinan bahwa masih ada pengguna yang merasa dikecewakan dengan pelayanan Shopee, hal inilah yang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 2 publications
0
5
0
4
Order By: Relevance
“…According to Davis TAM is an information systems theory designed to explain how an information technology can be understood and applied by its users. TAM is used to describe and estimate how the level of acceptance of the use of an information system, there are several bases used in this model to find out what factors affect the acceptance of a system, and then explain how an information system has a causal relationship with benefits and ease of use [9]. From the table 1 above, it can be concluded that based on the four indicator items in measuring the level of effectiveness of using the zoom meeting described above, it can be explained that the level of effectiveness is in the effective category with a percentage of 60.7% or 74 respondents, then continued with the very effective category.…”
Section: Resultsmentioning
confidence: 99%
“…According to Davis TAM is an information systems theory designed to explain how an information technology can be understood and applied by its users. TAM is used to describe and estimate how the level of acceptance of the use of an information system, there are several bases used in this model to find out what factors affect the acceptance of a system, and then explain how an information system has a causal relationship with benefits and ease of use [9]. From the table 1 above, it can be concluded that based on the four indicator items in measuring the level of effectiveness of using the zoom meeting described above, it can be explained that the level of effectiveness is in the effective category with a percentage of 60.7% or 74 respondents, then continued with the very effective category.…”
Section: Resultsmentioning
confidence: 99%
“…Sikap adalah perbuatan, perilaku atau gerak-gerik yang berdasarkan pada pendirian, pendapat atau keyakinan (Fiyah, Mayangky, Hadianti, dan Riana, 2019;Lee et al, 2017;Nanggala, 2020;Sanjaya, 2018). Banyak penelitian yang membuktikan bahwa faktor individu atau perilaku mempengaruhi pengadopsian teknologi informasi.…”
Section: Sikap Berkomputerunclassified
“…Pengguna cenderung akan menggunakan aplikasi jika aplikasi tersebut mudah digunakan dan bermanfaat. Metode TAM mendeskripsikan dan memperkirakan penerimaan user terhadap penggunaan suatu sistem /aplikasi, mengetahui faktor yang mempengaruhi keputusan pengguna untuk memutuskan kapan menggunakan aplikasi tersebut [18].…”
Section: Pendahuluanunclassified